Understanding the dehydrogenation properties of MgH2 catalysed by Na3AlF6. (22nd November 2019) - Halim Yap, F.A.; Sulaiman, N.N.; Ismail, M.
Abstract: The catalytic effect of Na3 AlF6 on the dehydrogenation properties of the MgH2 with X wt% (X = 5, 10, 20 and 50) have been investigated by ball milling technique. Based on the temperature-programme-desorption result, the addition of 10 wt% Na3 AlF6 to the MgH2 has demonstrated the best dehydrogenation properties performance. The dehydrogenation temperature of the un-doped MgH2 has experienced a reduction for about 60 °C after doped with 10 wt% Na3 AlF6 . The dehydrogenation kinetics also has been improved with the addition of 10 wt% Na3 AlF6 . Based on the Kissinger analysis, it was observed that the apparent activation energy of MgH2 desorption is remarkably decreased from 158 kJ/mol to 129 kJ/mol with the addition of 10 wt% Na3 AlF6 . Meanwhile, the formations of new species, the NaMgF3, the NaF and the AlF3 in the doped composite after the de/rehydrogenation processes are found in the X-ray diffraction analysis. These new species are expected to act as the active species that probably contributes to enhance the dehydrogenation properties of MgH2 . Highlights: The H2 storage properties of Na3 AlF6 -doped MgH2 have been studied. Dehydrogenation properties of MgH2 is improved after adding with Na3 AlF6 . EA for hydrogen desorption of MgH2 /Na3 AlF6 composite was lowered to 129.0 kJ/mol. The in - situ formation of the NaMgF3, NaF and AlF3 species play a synergetic role.